Evaluation of the Importance of Proper Health Education and Information on Lifestyle to be Adopted during Pregnancy - Maria Costantino; Antonio Raffone; Ilenia Stanzione; Daniela Siano; Rosa Oro; Valeria Conti; Graziamaria Corbi; Berenice Stefanelli; Mariagrazia Bathilde Marongiu; Domenico De Pascale; Carmine Sellitto; Vito Della Rocca; et al. (Clinical and Experimental Obstetrics & Gynecology)
Background: Proper health education and lifestyle information to be adopted during pregnancy are crucial for the well-being of the pregnant women and the health of the child. The aim of our study was to evaluate the impact of proper health education and lifestyle information to be adopted during pregnancy on obstetrical, neonatal and infant outcomes. Methods: A retrospective single-center cohort study was carried out including all consecutive pregnant women admitted to our Institution, from December 2019 to February 2021. The study outcomes were the difference in obstetrical, neonatal and infant outcomes between women differentiated by Body Mass Index (BMI) at the end of pregnancy (i.e., normal weight vs overweight, and normal weight vs obese), physical activity (yes vs no), and smoking during pregnancy (yes vs no). Results: Ninety-one women were included. Compared with normal weight women, obese women showed an increased incidence of major maternal pathologies (p = 0.048) and caesarean delivery (p = 0.042). Regarding physical activity, significant differences were observed between pregnant women who do and do not perform physical activity with a lower value of the incidence of spontaneous vaginal delivery (p = 0.025) in sedentary women. Compared with non-smoking groups, smoking women showed significantly higher BMI at the end of pregnancy (p = 0.036), lower neonatal weight (p = 0.001) and lower Apgar index (p = 0.033). Lastly, the percentage of infants with weight and height percentiles within the mean value did not differ significantly among mothers stratified by BMI, physical activity and smoking. Conclusions: Our data, in agreement with the literature, confirm that the proper information and education about lifestyle changes, particularly regarding BMI and smoking during pregnancy, can improve the health of the women and newborn.